Analisis pengaruh kinerja keuangan dan variabel makroekonomi terhadap Indeks Saham Syariah Indonesia - Arifudin, Royan; Rofiuddin, Mohammad (Journal of Economics Research and Policy Studies, 2022)
The condition of the Islamic capital market in Indonesia continues to improve, resulting in an increasing number of investors. Investors were interested in investing pay attention to various factors, both financial performance and macroeconomic factors. Good financial conditions and positive macroeconomic factors support investment, affecting the stock index. This study aims to determine the effect of financial performance and macroeconomic factors on the Indonesian Sharia Stock Index. The data used include the current ratio, debt-to-equity ratio, return on equity, inflation, exchange rates, interest rates, and the Indonesian Sharia Stock Index. The method used to measure the effect of the independent variable on the dependent is multiple linear regression. The results showed that the debt-to-equity and current ratios did not affect the ISSI index. While return on equity, inflation, and exchange rates, as well as BI7, affect the Indonesian Sharia stock index.